The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/2050-6511-14-5
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reaction monitoring: support for pharmacovigilance at a tertiary care hospital in Northern Brazil

Abstract: BackgroundAdverse drug reactions (ADRs) are recognised as a common cause of hospital admissions, and they constitute a significant economic burden for hospitals. Hospital-based ADR monitoring and reporting programmes aim to identify and quantify the risks associated with the use of drugs provided in a hospital setting. This information may be useful for identifying and minimising preventable ADRs and may enhance the ability of prescribers to manage ADRs more effectively. The main objectives of this study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
58
1
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 15 publications
(18 reference statements)
16
58
1
11
Order By: Relevance
“…Several other studies have also found similar results. [7][8][9] However, some studies showed female preponderance. 10,11 Thereby concluding that influence of gender is just an incidental finding and it does not affects number of ADR reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have also found similar results. [7][8][9] However, some studies showed female preponderance. 10,11 Thereby concluding that influence of gender is just an incidental finding and it does not affects number of ADR reported.…”
Section: Discussionmentioning
confidence: 99%
“…Muitos estudos sobre os EAM abordam o tema sob a perspectiva de um agravo durante a assistência hospitalar ou ambulatorial, ocorrendo em 3% a 18,3% do total de internações [6][7][8][9], mas não como causa de internações. Alguns estudos que investigaram as internações hospitalares tendo como motivo o uso prévio de medicamentos estimam uma variação de 0,5% a 32,9%, cuja diferença pode ser relacionada ao desenho do estudo, como a população amostral, os métodos de coleta e a seleção de dados [5].…”
Section: Discussionunclassified
“…A diferença, embora estatisticamente significativa, foi pequena, podendo ser considerada clinicamente irrelevante. Estudos publicados na literatura científica [8,11] não identificaram o sexo como fator de risco para EAM.…”
Section: Discussionunclassified
“…En cuanto a la gravedad, la mayoría de las reacciones adversas (69,5 %) se catalogó como moderada.En este punto es importante recordar que todas las notificaciones analizadas provenían de IPS de diferentes niveles de atención y no de la comunidad, por lo que existe la posibilidad de que las reacciones adversas leves, que corresponden a signos y síntomas que se resuelven espontáneamente, no lleguen a las IPS y, por lo tanto, no sean reportadas. Aun con esta salvedad, estos datos son similares a los reportados en otros estudios de farmacovigilancia, como el de Alves de Araujo en Brasil, entre otros (26)(27)(28).…”
Section: Discussionunclassified